(untitled) (Economic and Political Thought, 2022)
The British Climate Change Act created the world’s first long-term institutional and legal system aimed at reducing domestic greenhouse gas emissions. Following its 2019 amendment, the UK also became the first G7 and G20 country to commit to climate neutrality. The Act, described as one of the most advanced legal acts in the field of climate policy, is still a reference point and source of inspiration for many countries around the world. The model established by it, however, struggles with the credible commitment problem, and the structural problems arising, inter alia, from the aforementioned amendment and the departure of the UK from the European Union may in the future additionally weaken its credibility and have a negative impact not only on British but also on global climate action. The aim of this article is to present the main elements of the British model of climate policy and to signal future challenges to its credibility against the background of the previous experience with the implementation of the Act and the latest emissions reduction targets announced at the end of 2020 and in the first half of 2021.